Hadith #4859 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
A group of three men came to the houses of the wives of the Prophet (ï·º) asking how the Prophet (ï·º) worshipped (Allah), and when they were informed about that, they considered their worship insufficient and said, âWhere are we from the Prophet (ï·º) as his past and future sins have been forgiven.â Then one of them said, âI will offer the prayer throughout the night forever.â The other said, âI will fast throughout the year and will not break my fast.â The third said, âI will kee
Grade: Sahih

Hadith #4860 - Sahih al-Bukhari - 'Urwa Al-Bariqi (Sahih al-Bukhari)
that he asked `Aisha about the Statement of Allah: âIf you fear that you shall not be able to deal justly with the orphan girls, then marry (other) women of your choice, two or three or four; but if you fear that you shall not be able to deal justly (with them), then only one, or (the captives) that your right hands possess. That will be nearer to prevent you from doing injustice.â (4.3) `Aisha said, âO my nephew! (This Verse has been revealed in connection with) an orphan girl under the g
Grade: Sahih

Hadith #4861 - Sahih al-Bukhari - `Alqamah bin Waqqas al Laithi said that he heard `Umar bin al-Khattab addressing the people (Sahih al-Bukhari)
While I was with `Abdullah, `Uthman met him at Mina and said, âO Abu `Abdur-Rahman ! I have something to say to you.â So both of them went aside and `Uthman said, âO Abu `Abdur-Rah. man! Shall we marry you to a virgin who will make you remember your past days?â When `Abdullah felt that he was not in need of that, he beckoned me (to join him) saying, âO âAlqama!â Then I heard him saying (in reply to `Uthman), âAs you have said that, (I tell you that) the Prophet (ï·º) once said to
Grade: Sahih

Hadith #4862 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
We were with the Prophet (ï·º) while we were young and had no wealth. So Allahâs Messenger (ï·º) said, âO young people! Whoever among you can marry, should marry, because it helps him lower his gaze and guard his modesty (i.e. his private parts from committing illegal sexual intercourse etc.), and whoever is not able to marry, should fast, as fasting diminishes his sexual power.â
Grade: Sahih

Hadith #4863 - Sahih al-Bukhari - âAta` bin Farrookh (Sahih al-Bukhari)
We presented ourselves along with Ibn `Abbas at the funeral procession of Maimuna at a place called Sarif. Ibn `Abbas said, âThis is the wife of the Prophet (ï·º) so when you lift her bier, do not Jerk it or shake it much, but walk smoothly because the Prophet (ï·º) had nine wives and he used to observe the night turns with eight of them, and for one of them there was no night turn.â
Grade: Sahih

Hadith #4864 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) used to go round (have sexual relations with) all his wives in one night, and he had nine wives.
Grade: Sahih

Hadith #4865 - Sahih al-Bukhari - S'aid bin Qays bin Qahd Ø³Ø¹ÙØ¯ Ø¨Ù ÙÙØ³ Ø¨Ù ÙÙØ¯ Ø§ÙØ£ÙØµØ§Ø±Ù (Sahih al-Bukhari)
Ibn `Abbas asked me, âAre you married?â I replied, âNo.â He said, âMarry, for the best person of this (Muslim) nation (i.e., Muhammad) of all other Muslims, had the largest number of wives.â
Grade: Sahih

Hadith #4866 - Sahih al-Bukhari - Umar ibn al-Khattab (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe rewards (of deeds) are according to the intention, and everybody will get the reward for what he has intended. So whoever emigrated for Allahâs and His Apostleâs sake, his emigration was for Allah and His Apostle; and whoever emigrated for worldly benefits, or to marry a woman, then his emigration was for the thing for what he emigrated for.â (1)
Grade: Sahih

Hadith #4867 - Sahih al-Bukhari - ibn Mas'ud (Sahih al-Bukhari)
We used to fight in the holy battles in the company of the Prophet (ï·º) and we had no wives with us. So we said, âO Allahâs Messenger (ï·º)! Shall we get castrated?â The Prophet (ï·º) forbade us to do so.
Grade: Sahih

Hadith #4868 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
`Abdur-Rahman bin `Auf came (from Mecca to Medina) and the Prophet (ï·º) made a bond of brotherhood between him and Sa`d bin Ar-Rabi` Al-Ansari. Al-Ansari had two wives, so he suggested that `Abdur- Rahman take half, his wives and property. `Abdur-Rahman replied, âMay Allah bless you with your wives and property. Kindly show me the market.â So `Abdur-Rahman went to the market and gained (in bargains) some dried yoghurt and some butter. After a few days the Prophet (ï·º) saw `Abdur-Rahman wit
Grade: Sahih

Hadith #4869 - Sahih al-Bukhari - Sa'd ibn Abi Waqqas (Sahih al-Bukhari)
Allahâs Messenger (ï·º) forbade `Uthman bin Mazâun to abstain from marrying (and other pleasures) and if he had allowed him, we would have gotten ourselves castrated.
Grade: Sahih

Hadith #4870 - Sahih al-Bukhari - Sa'd ibn Abi Waqqas (Sahih al-Bukhari)
The Prophet (ï·º) prevented `Uthman bin Mazun from that (not marrying), and had he allowed him, we would have got ourselves castrated.
Grade: Sahih

Hadith #4871 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
We used to participate in the holy battles led by Allahâs Messenger (ï·º) and we had nothing (no wives) with us. So we said, âShall we get ourselves castrated?â He forbade us that and then allowed us to marry women with a temporary contract (2) and recited to us: â âO you who believe ! Make not unlawful the good things which Allah has made lawful for you, but commit no transgression.â (5.87)
Grade: Sahih

Hadith #4872 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
I said, âO Allahâs Messenger (ï·º)! I am a young man and I am afraid that I may commit illegal sexual intercourse and I cannot afford to marry.â He kept silent, and then repeated my question once again, but he kept silent. I said the same (for the third time) and he remained silent. Then repeated my question (for the fourth time), and only then the Prophet said, âO Abu Huraira! The pen has dried after writing what you are going to confront. So (it does not matter whether you) get yoursel
Grade: Sahih

Hadith #4873 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
I said, âO Allahâs Messenger (ï·º)! Suppose you landed in a valley where there is a tree of which something has been eaten and then you found trees of which nothing has been eaten, of which tree would you let your camel graze?â He said, â(I will let my camel graze) of the one of which nothing has been eaten before.â (The sub-narrator added: `Aisha meant that Allahâs Messenger (ï·º) had not married a virgin besides herself .)
Grade: Sahih

Hadith #4874 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said (to me), âYou have been shown to me twice in (my) dreams. A man was carrying you in a silken cloth and said to me, âThis is your wife.â I uncovered it; and behold, it was you. I said to myself, âIf this dream is from Allah, He will cause it to come true.â â
Grade: Sahih

Hadith #4875 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
While we were returning from a Ghazwa (Holy Battle) with the Prophet, I started driving my camel fast, as it was a lazy camel A rider came behind me and pricked my camel with a spear he had with him, and then my camel started running as fast as the best camel you may see. Behold! The rider was the Prophet (ï·º) himself. He said, âWhat makes you in such a hurry?â I replied, I am newly married â He said, âDid you marry a virgin or a matron? I replied, âA matron.â He said, âWhy didnâ
Grade: Sahih

Hadith #4876 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
When I got married, Allahâs Messenger (ï·º) said to me, âWhat type of lady have you married?â I replied, âI have married a matronâ He said, âWhy, donât you have a liking for the virgins and for fondling them?â Jabir also said: Allahâs Messenger (ï·º) said, âWhy didnât you marry a young girl so that you might play with her and she with you?â
Grade: Sahih

Hadith #4877 - Sahih al-Bukhari - 'Urwa Al-Bariqi (Sahih al-Bukhari)
The Prophet (ï·º) asked Abu Bakr for `Aishaâs hand in marriage. Abu Bakr said âBut I am your brother.â The Prophet (ï·º) said, âYou are my brother in Allahâs religion and His Book, but she (Aisha) is lawful for me to marry.â
Grade: Sahih

Hadith #4878 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe best women are the riders of the camels and the righteous among the women of Quraish. They are the kindest women to their children in their childhood and the more careful women of the property of their husbands.â
Grade: Sahih

Hadith #4879 - Sahih al-Bukhari - Abu Burda's father (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, any man who has a slave girl whom he educates properly, teaches good manners, manumits and marries her, will get a double reward And if any man of the people of the Scriptures believes in his own prophet and then believes in me too, he will (also) get a double reward And any slave who fulfills his duty to his master and to his Lord, will (also) get a double reward.â
Grade: Sahih

Hadith #4880 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said: Abraham did not tell lies except three. (One of them was) when Abraham passed by a tyrant and (his wife) Sara was accompanying him (Abu Huraira then mentioned the whole narration and said:) (The tyrant) gave her Hajar. Sara said, âAllah saved me from the hands of the Kafir (i.e. infidel) and gave me Hajar to serve me.â (Abu Huraira added:) That (Hajar) is your mother, O Banu Maâ-As-Samaâ (i.e., the Arabs).
Grade: Sahih

Hadith #4881 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) stayed for three days between Khaibar and Medina, and there he consummated his marriage to Safiyya bint Huyai. I invited the Muslims to the wedding banquet in which neither meat nor bread was offered. He ordered for leather dining-sheets to be spread, and dates, dried yoghurt and butter were laid on it, and that was the Prophetâs wedding banquet. The Muslims wondered, âIs she (Saffiyya) considered as his wife or his slave girl?â Then they said, âIf he orders her to veil
Grade: Sahih

Hadith #4882 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allahâs Messenger (ï·º) manumitted Safiyya and regarded her manumission as her Mahr.
Grade: Sahih

Hadith #4883 - Sahih al-Bukhari - Sahl bin 'Uthman bin Fars Ø³ÙÙ Ø¨Ù Ø¹Ø«ÙØ§Ù Ø¨Ù ÙØ§Ø±Ø³ (Sahih al-Bukhari)
A woman came to Allahâs Messenger (ï·º) and said, âO Allahâs Messenger (ï·º)! I have come to give you myself in marriage (without Mahr).â Allahâs Messenger (ï·º) looked at her. He looked at her carefully and fixed his glance on her and then lowered his head. When the lady saw that he did not say anything, she sat down. A man from his companions got up and said, âO Allahâs Messenger (ï·º)! If you are not in need of her, then marry her to me.â The Prophet (ï·º) said, âHave you go
Grade: Sahih

Hadith #4884 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Abu Hudhaifa bin `Utba bin Rabi`a bin `Abdi Shams who had witnessed the battle of Badr along with the Prophet (ï·º) adopted Salim as his son, to whom he married his niece, Hind bint Al-Walid bin `Utba bin Rabi`a; and Salim was the freed slave of an Ansar woman, just as the Prophet (ï·º) had adopted Zaid as his son. It was the custom in the Pre-lslamic Period that if somebody adopted a boy, the people would call him the son of the adoptive father and he would be the latterâs heir. But when Alla
Grade: Sahih

Hadith #4885 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Allahâs Messenger (ï·º) entered upon Dubaa bint Az-Zubair and said to her, âDo you have a desire to perform the Hajj?â She replied, âBy Allah, I feel sick.â He said to her, âIntend to perform Hajj and stipulate something by saying, âO Allah, I will finish my Ihram at any place where You stop me (i.e. I am unable to go further).â She was the wife of Al-Miqdad bin Al-Aswad.
Grade: Sahih

Hadith #4886 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âA woman is married for four things, i.e., her wealth, her family status, her beauty and her religion. So you should marry the religious woman (otherwise) you will be a losers.
Grade: Sahih

Hadith #4887 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
A man passed by Allahâs Messenger (ï·º) and Allah s Apostle asked (his companions) âWhat do you say about this (man)?â They replied âIf he asks for a ladyâs hand, he ought to be given her in marriage; and if he intercedes (for someone) his intercessor should be accepted; and if he speaks, he should be listened to.â Allahâs Messenger (ï·º) kept silent, and then a man from among the poor Muslims passed by, an Allahâs Apostle asked (them) âWhat do you say about this man?â They r
Grade: Sahih

Hadith #4888 - Sahih al-Bukhari - 'Urwa Al-Bariqi (Sahih al-Bukhari)
that he asked `Aisha regarding the Verse: âIf you fear that you shall not be able to deal justly with the orphans (4.3) She said, âO my nephew! This Verse refers to the orphan girl who is under the guardianship of her guardian who likes her beauty and wealth and wishes to (marry her and) curtails her Mahr. Such guardians have been forbidden to marry them unless they do justice by giving them their full Mahr, and they have been ordered to marry other than them. The people asked for the verdic
Grade: Sahih

Hadith #4889 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âEvil omen is in the women, the house and the horse.â
Grade: Sahih

Hadith #4890 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Evil omen was mentioned before the Prophet: The Prophet (ï·º) said, âIf there is evil omen in anything, it is in the house, the woman and the horse.â
Grade: Sahih

Hadith #4891 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âIf at all there is bad omen, it is in the horse, the woman, and the house.â
Grade: Sahih

Hadith #4892 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
The Prophet (ï·º) said, âAfter me I have not left any trial more severe to men than women.â
Grade: Sahih

Hadith #4893 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Three principles were established because of Barira: (i) When Banra was manumitted she was given the option (to remain with her slave husband or not). (ii) Allahâs Messenger (ï·º) said âThe Wala of the slave) is for the one who manumits (the slave). (iii) When Allahâs Messenger (ï·º) entered (the house), he saw a cooking pot on the fire but he was given bread and meat soup from the soup of the home. The Prophet (ï·º) said, âDidnât I see the cooking pot (on the fire)?â It was said, â
Grade: Sahih

Hadith #4894 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
(regarding) the Verse: âAnd if you fear that you shall not be able to deal justly with the orphansâ¦â (4.3) It is about the orphan girl who is in the custody of a man who is her guardian, and he intends to marry her because of her wealth, but he treats her badly and does not manage her property fairly and honestly. Such a man should marry women of his liking other than her, two or three or four. âProhibited to you (for marriage) are: â¦your foster-mothers (who suckled you).â (4.23) Mar
Grade: Sahih

Hadith #4895 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
(the wife of the Prophet) that while Allahâs Messenger (ï·º) was with her, she heard a voice of a man asking permission to enter the house of Hafsa. `Aisha added: I said, âO Allahâs Messenger (ï·º)! This man is asking permission to enter your house.â The Prophet (ï·º) said, âI think he is so-and-so,â naming the foster-uncle of Hafsa. `Aisha said, âIf so-and-so,â naming her foster uncle, âwere living, could he enter upon me?â The Prophet (ï·º) said, âYes, for foster suckling
Grade: Sahih

Hadith #4896 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
It was said to the Prophet, âWonât you marry the daughter of Hamza?â He said, âShe is my foster niece (brotherâs daughter). â
Grade: Sahih

Hadith #4897 - Sahih al-Bukhari - Um Habiba (Sahih al-Bukhari)
(daughter of Abu Sufyan) I said, âO Allahâs Messenger (ï·º)! Marry my sister. the daughter of Abu Sufyan.â The Prophet (ï·º) said, âDo you like that?â I replied, âYes, for even now I am not your only wife and I like that my sister should share the good with me.â The Prophet (ï·º) said, âBut that is not lawful for me.â I said, We have heard that you want to marry the daughter of Abu Salama.â He said, â(You mean) the daughter of Um Salama?â I said, âYes.â He said, âEv
Grade: Sahih

Hadith #4898 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
that the Prophet (ï·º) entered upon her while a man was sitting with her. Signs of answer seemed to appear on his face as if he disliked that. She said, âHere is my (foster) brother.â He said, âBe sure as to who is your foster brother, for foster suckling relationship is established only when milk is the only food of the child.â
Grade: Sahih

Hadith #4899 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
that Aflah the brother of Abu Al-Quâais, her foster uncle, came, asking permission to enter upon her after the Verse of Al-Hijab (the use of veils by women) was revealed. `Aisha added: I did not allow him to enter, but when Allahâs Messenger (ï·º) came, I told him what I had done, and he ordered me to give him permission.
Grade: Sahih

Hadith #4900 - Sahih al-Bukhari - Uqba bin 'Alqama al-Ma'fari Ø¹ÙØ¨Ø© Ø¨Ù Ø¹ÙÙÙØ© Ø¨Ù ØØ¯ÙØ¬ Ø§ÙÙØ¹Ø§ÙØ±Ù (Sahih al-Bukhari)
I married a woman and then a black lady came to us and said, âI have suckled you both (you and your wife).â So I came to the Prophet (ï·º) and said, âI married so-and-so and then a black lady came to us and said to me, âI have suckled both of you.â But I think she is a liar.â The Prophet (ï·º) turned his face away from me and I moved to face his face, and said, âShe is a liar.â The Prophet (ï·º) said, âHow (can you keep her as your wife) when that lady has said that she has suc
Grade: Sahih

Hadith #4901 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
âForbidden for you (for marriages) are your mothersâ¦â (4:23). âAbdullah bin Jaâfar married the daughter and wife of âAli at the same time (they were step-daughter and mother). Ibn Sirin said, âThere is no harm in that.â But Al-Hasan Al-Basri disapproved of it at first, but then said that there was no harm in it. Al-Hasan bin Al-Hasan bin âAli married two of his cousins in one night. Jaâfar bin Zaid disapproved of that because of it would bring hatred (between the two cousins)
Grade: Sahih

Hadith #4902 - Sahih al-Bukhari - Um Habiba (Sahih al-Bukhari)
I said, âO Allahâs Messenger (ï·º)! Do you like to have (my sister) the daughter of Abu Sufyan?â The Prophet (ï·º) said, âWhat shall I do (with her)?â I said, âMarry her.â He said, âDo you like that?â I said, â(Yes), for even now I am not your only wife, so I like that my sister should share you with me.â He said, âShe is not lawful for me (to marry).â I said, âWe have heard that you want to marry.â He said, âThe daughter of Um Salama?â I said, âYes.â He sai
Grade: Sahih

Hadith #4903 - Sahih al-Bukhari - Um Habiba (Sahih al-Bukhari)
I said, âO Allahâs Messenger (ï·º)! Marry my sister, the daughter of Abu Sufyan.â He said, âDo you like that?â I said, âYes, for even now I am not your only wife; and the most beloved person to share the good with me is my sister.â The Prophet (ï·º) said, âBut that is not lawful for me (i.e., to be married to two sisters at a time.)â I said, âO Allahâs Messenger (ï·º)! By Allah, we have heard that you want to marry Durra, the daughter of Abu Salama.â He said, âYou mean
Grade: Sahih

Hadith #4904 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) forbade that a woman should be married to man along with her paternal or maternal aunt.
Grade: Sahih

Hadith #4905 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âA woman and her paternal aunt should not be married to the same man; and similarly, a woman and her maternal aunt should not be married to the same man.â
Grade: Sahih

Hadith #4906 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) forbade that a woman should be married to a man along with her paternal aunt or with her maternal aunt (at the same time). Az-Zuhri (the sub-narrator) said: There is a similar order for the paternal aunt of the father of oneâs wife, for âUrwa told me that `Aisha said, âWhat is unlawful because of blood relations, is also unlawful because of the corresponding foster suckling relations.â
Grade: Sahih

Hadith #4907 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allahâs Messenger (ï·º) forbade Ash-Shighar, which means that somebody marries his daughter to somebody else, and the latter marries his daughter to the former without paying Mahr.
Grade: Sahih

Hadith #4908 - Sahih al-Bukhari - Hisham's father (Sahih al-Bukhari)
Khaula bint Hakim was one of those ladies who presented themselves to the Prophet (ï·º) for marriage. `Aisha said, âDoesnât a lady feel ashamed for presenting herself to a man?â But when the Verse: â(O Muhammad) You may postpone (the turn of) any of them (your wives) that you please,â (33.51) was revealed, â `Aisha said, âO Allahâs Messenger (ï·º)! I do not see, but, that your Lord hurries in pleasing you.â â
Grade: Sahih

Hadith #4909 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ï·º) got married while he was in the state of Ihram.
Grade: Sahih

Hadith #4910 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I said to Ibn `Abbas, âDuring the battle of Khaibar the Prophet (ï·º) forbade (Nikah) Al-Mutâa and the eating of donkeyâs meat.â
Grade: Sahih

Hadith #4911 - Sahih al-Bukhari - Abu Jamra Ad-Dabi (Sahih al-Bukhari)
I heard Ibn `Abbas (giving a verdict) when he was asked about the Mutâa with the women, and he permitted it (Nikah-al-Mutâa). On that a freed slave of his said to him, âThat is only when it is very badly needed and women are scarce.â On that, Ibn `Abbas said, âYes.â
Grade: Sahih

Hadith #4912 - Sahih al-Bukhari (Sahih al-Bukhari)
While we were in an army, Allahâs Messenger (ï·º) came to us and said, âYou have been allowed to do the Mutâa (marriage), so do it.â
Grade: Sahih

Hadith #4913 - Sahih al-Bukhari - Salama bin 'Alqama (Sahih al-Bukhari)
Allahâs Messenger (ï·º)âs said, âIf a man and a woman agree (to marry temporarily), their marriage should last for three nights, and if they like to continue, they can do so; and if they want to separate, they can do so.â I do not know whether that was only for us or for all the people in general. Abu `Abdullah (Al-Bukhari) said: `Ali made it clear that the Prophet said, âThe Mutâa marriage has been cancelled (made unlawful).
Grade: Sahih

Hadith #4914 - Sahih al-Bukhari - Thabit Al-Bunani (Sahih al-Bukhari)
I was with Anas while his daughter was present with him. Anas said, âA woman came to Allahâs Apostle and presented herself to him, saying, âO Allahâs Messenger (ï·º), have you any need for me (i.e. would you like to marry me)?â âThereupon Anasâs daughter said, âWhat a shameless lady she was ! Shame! Shame!â Anas said, âShe was better than you; she had a liking for the Prophet (ï·º) so she presented herself for marriage to him.â
Grade: Sahih

Hadith #4915 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
A woman presented herself to the Prophet (for marriage). A man said to him, âO Allahâs Messenger (ï·º)! (If you are not in need of her) marry her to me.â The Prophet (ï·º) said, âWhat have you got?â The man said, âI have nothing.â The Prophet (ï·º) said (to him), âGo and search for something) even if it were an iron ring.â The man went and returned saying, âNo, I have not found anything, not even an iron ring; but this is my (Izar) waist sheet, and half of it is for her.â H
Grade: Sahih

Hadith #4916 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
`Umar bin Al-Khattab said, âWhen Hafsa bint `Umar became a widow after the death of (her husband) Khunais bin Hudhafa As-Sahmi who had been one of the companions of the Prophet, and he died at Medina. I went to `Uthman bin `Affan and presented Hafsa (for marriage) to him. He said, âI will think it over.â I waited for a few days, then he met me and said, âIt seems that it is not possible for me to marry at present.â â `Umar further said, âI met Abu Bakr As-Siddique and said to him,
Grade: Sahih

Hadith #4917 - Sahih al-Bukhari - Zainab bint Salama (Sahih al-Bukhari)
Um Habiba said to Allahâs Messenger (ï·º) âWe have heard that you want to marry Durra bint Abu-Salama.â Allahâs Messenger (ï·º) said, âCan she be married along with Um Salama (her mother)? Even if I have not married Um Salama, she would not be lawful for me to marry, for her father is my foster brother.â
Grade: Sahih

Hadith #4918 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
âHint your intention of marryingâ is made by saying (to the widow) for example: âI want to marry, and I wish that Allah will make a righteous lady available for me.â â Al-Qasim said: One may say to the widow: âI hold all respect for you, and I am interested in you; Allah will bring you much good, or something similar âAta said: One should hint his intention, and should not declare it openly. One may say: âI have some need. Have good tidings. Praise be to Allah; you are fit to rem
Grade: Sahih

Hadith #4919 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said (to me), âYou were shown to me in a dream. An angel brought you to me, wrapped in a piece of silken cloth, and said to me, âThis is your wife.â I removed the piece of cloth from your face, and there you were. I said to myself. âIf it is from Allah, then it will surely be.â â
Grade: Sahih

Hadith #4920 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
A woman came to Allahâs Messenger (ï·º) and said, âO Allahâs Messenger (ï·º)! I have come to you to present myself to you (for marriage).â Allahâs Messenger (ï·º) glanced at her. He looked at her carefully and fixed his glance on her and then lowered his head. When the lady saw that he did not say anything, she sat down. A man from his companions got up and said, âO Allahâs Messenger (ï·º)! If you are not in need of her, then marry her to me.â The Prophet (ï·º) said, âHave you
Grade: Sahih

Hadith #4921 - Sahih al-Bukhari - Urwa bin 'Abdullah Ø¹Ø±ÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØ´ÙØ± (Sahih al-Bukhari)
âAishah, the wife of the Prophet (ï·º) told him that there were four types of marriage during Pre-Islamic period of Ignorance. One type was similar to that of the present day i.e. a man used to ask somebody else for the hand of a girl under his guardianship or for his daughterâs hand, and give her Mahr and then marry her. The second type was that a man would say to his wife after she had become clean from her period. âSend for so-and-so and have sexual intercourse with him.â Her husband
Grade: Sahih

Hadith #4922 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
(as regards the Verse): âAnd about what is recited unto you in the Book, concerning orphan girls to whom you give not the prescribed portions and yet, whom you desire to marry.â (4.127) This Verse is about the female orphan who is under the guardianship of a man with whom she shares her property and he has more right over her (than anybody else) but does not like to marry her, so he prevents her, from marrying somebody else, lest he should share the property with him.
Grade: Sahih

Hadith #4923 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
When Hafsa, `Umarâs daughter became a widow because of the death of her (husband) Ibn Hudhafa As-Sahmi who was one of the companion of the Prophet (ï·º) and the one of the Badr warriors and died at Medina, `Umar said, âI met `Uthman bin `Affan and gave him an offer, saying, âIf you wish, I will marry Hafsa to you.â He said. âI will think it overâ I waited for a few days, then he met me and said, âI have made up my mind not to marry at presentâ â`Umar added, âThen I met Abu Ba
Grade: Sahih

Hadith #4924 - Sahih al-Bukhari - al-Hasan al-Basri Ø§ÙØØ³Ù Ø§ÙØ¨ØµØ±Ù (Sahih al-Bukhari)
concerning the Verse: âDo not prevent themâ (2.232) Maâqil bin Yasar told me that it was revealed in his connection. He said, âI married my sister to a man and he divorced her, and when her days of âIdda (three menstrual periods) were over, the man came again and asked for her hand, but I said to him, âI married her to you and made her your bed (your wife) and favored you with her, but you divorced her. Now you come to ask for her hand again? No, by Allah, she will never go back to y
Grade: Sahih

Hadith #4925 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
(regarding His Statement): âThey ask your instruction concerning the women. Say: Allah instructs you about them â¦â (4.127) It is about the female orphan who is under the guardianship of a man with whom she shares her property and he does not want to marry her and dislikes that someone else should marry her, lest he should share the property with him, so he prevents her from marrying. So Allah forbade such a guardian to do so (i.e. to prevent her from marrying).
Grade: Sahih

Hadith #4926 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
While we were sitting in the company of the Prophet (ï·º) a woman came to him and presented herself (for marriage) to him. The Prophet (ï·º) looked at her, lowering his eyes and raising them, but did not give a reply. One of his companions said, âMarry her to me O Allahâs Messenger (ï·º)!â The Prophet (ï·º) asked (him), âHave you got anything?â He said, âI have got nothing.â The Prophet (ï·º) said, âNot even an iron ring?â He Sa`d, âNot even an iron ring, but I will tear my g
Grade: Sahih

Hadith #4927 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
that the Prophet (ï·º) married her when she was six years old and he consummated his marriage when she was nine years old, and then she remained with him for nine years (i.e., till his death).
Grade: Sahih

Hadith #4928 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
that the Prophet (ï·º) married her when she was six years old and he consummated his marriage when she was nine years old. Hisham said: I have been informed that `Aisha remained with the Prophet (ï·º) for nine years (i.e. till his death).
Grade: Sahih

Hadith #4929 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
A woman came to Allahâs Messenger (ï·º) and said, âI present myself (to you) (for marriage). She stayed for a long while, then a man said, âIf you are not in need of her then marry her to me.â The Prophet (ï·º) said, âHave you got anything m order to pay her Mahr?â He said, âI have nothing with me except my Izar (waist sheet).â The Prophet (ï·º) said, âIf you give her your Izar, you will have no Izar to wear, (so go) and search for something. He said, âI could not find anythi
Grade: Sahih

Hadith #4930 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âA matron should not be given in marriage except after consulting her; and a virgin should not be given in marriage except after her permission.â The people asked, âO Allahâs Messenger (ï·º)! How can we know her permission?â He said, âHer silence (indicates her permission).
Grade: Sahih

Hadith #4931 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
I said, âO Allahâs Messenger (ï·º)! A virgin feels shy.â He said, âHer consent is (expressed by) her silence.â
Grade: Sahih

Hadith #4932 - Sahih al-Bukhari - Khansa bint Khudham al-Ansariyya (Sahih al-Bukhari)
that her father gave her in marriage when she was a matron and she disliked that marriage. So she went to Allahâs Messenger (ï·º) and he declared that marriage invalid.
Grade: Sahih

Hadith #4933 - Sahih al-Bukhari (Sahih al-Bukhari)
The same ,Hadith above: A man called Khidam married a daughter of his (to somebody) against her consent. âIf you fear that you shall not be able to deal justly with the orphan girls then marry (other) women of your choice.â (4.3) And if somebody says to the guardian (of a woman), âMarry me to soand- so,â and the guardian remained silent or said to him, âWhat have you got?â And the other said, âI have so much and so much (Mahr),â or kept quiet, and then the guardian said, âI hav
Grade: Sahih

Hadith #4934 - Sahih al-Bukhari - Urwa bin 'Abdullah Ø¹Ø±ÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØ´ÙØ± (Sahih al-Bukhari)
that he asked `Aisha, saying to her, âO Mother! (In what connection was this Verse revealed): âIf you fear that you shall not be able to deal justly with orphan girls (to the end of the verse) that your right hands possess?â (4.3) Aisha said, âO my nephew! It was about the female orphan under the protection of her guardian who was interested in her beauty and wealth and wanted to marry her with a little or reduced Mahr. So such guardians were forbidden to marry female orphans unless they
Grade: Sahih

Hadith #4935 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
A woman came to the Prophet,, and presented herself to him (for marriage). He said, âI am not in need of women these days.â Then a man said, âO Allahâs Messenger (ï·º)! Marry her to me.â The Prophet (ï·º) asked him, âWhat have you got?â He said, âI have got nothing.â The Prophet (ï·º) said, âGive her something, even an iron ring.â He said, âI have got nothing.â The Prophet (ï·º) asked (him), âHow much of the Qurâan do you know (by heart)?â He said, âSo much and
Grade: Sahih

Hadith #4936 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
The Prophet (ï·º) decreed that one should not try to cancel a bargain already agreed upon between some other persons (by offering a bigger price). And a man should not ask for the hand of a girl who is already engaged to his Muslim brother, unless the first suitor gives her up, or allows him to ask for her hand.
Grade: Sahih

Hadith #4937 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âBeware of suspicion (about others), as suspicion is the falsest talk, and do not spy upon each other, and do not listen to the evil talk of the people about othersâ affairs, and do not have enmity with one another, but be brothers. And none should ask for the hand of a girl who is already engaged to his (Muslim) brother, but one should wait till the first suitor marries her or leaves her.â
Grade: Sahih

Hadith #4938 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
âWhen Hafsa became a widow,â `Umar said, âI met Abu Bakr and said to him, âIf you wish I will marry Hafsa bint `Umar to you.â I waited for a few days then Allahâs Messenger (ï·º) asked for her hand. Later Abu Bakr met me and said, âNothing stopped me from returning to you concerning your offer except that I knew that Allahâs Messenger (ï·º) had mentioned (his wish to marry) her, and I could never let out the secret of Allahâs Messenger (ï·º) . If he had left her, I would have a
Grade: Sahih

Hadith #4939 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Two men came from the east and delivered speeches, and the Prophet (ï·º) said, âSome eloquent speech has the influence of magic.â (e.g., some people refuse to do something and then a good eloquent speaker addresses them and then they agree to do that very thing after his speech)
Grade: Sahih

Hadith #4940 - Sahih al-Bukhari - Ar-Rabi'bint Mu'auwidh (Sahih al-Bukhari)
(the daughter of Muawwidh bin Afra) After the consummation of my marriage, the Prophet (ï·º) came and sat on my bed as far from me as you are sitting now, and our little girls started beating the tambourines and reciting elegiac verses mourning my father who had been killed in the battle of Badr. One of them said, âAmong us is a Prophet who knows what will happen tomorrow.â On that the Prophet said, âLeave this (saying) and keep on saying the verses which you had been saying before.â
Grade: Sahih

Hadith #4941 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
`Abdur Rahman bin `Auf married a woman and gave her gold equal to the weight of a date stone (as Mahr). When the Prophet (ï·º) noticed the signs of cheerfulness of the marriage (on his face) and asked him about it, he said, âI have married a woman and gave (her) gold equal to a date stone in weight (as Mahr).
Grade: Sahih

Hadith #4942 - Sahih al-Bukhari - Sahl bin 'Uthman bin Fars Ø³ÙÙ Ø¨Ù Ø¹Ø«ÙØ§Ù Ø¨Ù ÙØ§Ø±Ø³ (Sahih al-Bukhari)
While I was (sitting) among the people in the company of Allahâs Messenger (ï·º) a woman stood up and said, âO Allahâs Messenger (ï·º)! She has given herself in marriage to you; please give your opinion of her.â The Prophet did not give her any reply. She again stood up and said, âO Allahâs Messenger (ï·º)! She has given herself (in marriage) to you; so please give your opinion of her. The Prophet (ï·º) did not give her any reply. She again stood up for the third time and said, âSh
Grade: Sahih

Hadith #4943 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
The Prophet (ï·º) said to a man, âMarry, even with (a Mahr equal to) an iron ring.â
Grade: Sahih

Hadith #4944 - Sahih al-Bukhari - Uqba bin 'Alqama al-Ma'fari Ø¹ÙØ¨Ø© Ø¨Ù Ø¹ÙÙÙØ© Ø¨Ù ØØ¯ÙØ¬ Ø§ÙÙØ¹Ø§ÙØ±Ù (Sahih al-Bukhari)
The Prophet (ï·º) said: âThe stipulations most entitled to be abided by are those with which you are given the right to enjoy the (womenâs) private parts (i.e. the stipulations of the marriage contract).
Grade: Sahih

Hadith #4945 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âIt is not lawful for a woman (at the time of wedding) to ask for the divorce of her sister (i.e. the other wife of her would-be husband) in order to have everything for herself, for she will take only what has been written for her.â
Grade: Sahih

Hadith #4946 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
`Abdur-Rahman bin `Auf came to Allahâs Messenger (ï·º) and he had marks of Sufra (yellow perfume). Allahâs Messenger (ï·º) asked him (about those marks). `AbdurRahman bin `Auf told him that he had married a woman from the Ansar. The Prophet (ï·º) asked, âHow much Mahr did you pay her?â He said, âI paid gold equal to the weight of a date stone.â Allahâs Messenger (ï·º) said to him, âGive a wedding banquet, even if with one sheep.â
Grade: Sahih

Hadith #4947 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) offered a wedding banquet on the occasion of his marriage to Zainab, and provided a good meal for the Muslims. Then he went out as was his custom on marrying, he came to the dwelling places of the mothers of the Believers (i.e. his wives) invoking good (on them), and they were invoking good (on him). Then he departed (and came back) and saw two men (still sitting there). So he left again. I do not remember whether I informed him or he was informed (by somebody else) of their de
Grade: Sahih

Hadith #4948 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) saw the traces of Sufra (yellow perfume) on `Abdur-Rahman bin `Auf and said, âWhat is this?â `Abdur-Rahman, said, âI have married a woman and have paid gold equal to the weight of a datestone (as her Mahr). The Prophet (ï·º) said to him, âMay Allah bless you: Offer a wedding banquet even with one sheep.â
Grade: Sahih

Hadith #4949 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
When the Prophet (ï·º) married me, my mother came to me and made me enter the house where I saw some women from the Ansar who said, âMay you prosper and have blessings and have good omen.â
Grade: Sahih

Hadith #4950 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âA prophet among the prophets went for a military expedition and said to his people: âA man who has married a lady and wants to consummate his marriage with her and he has not done so yet, should not accompany me.â â
Grade: Sahih

Hadith #4951 - Sahih al-Bukhari - 'Urwa Al-Bariqi (Sahih al-Bukhari)
The Prophet (ï·º) wrote the (marriage contract) with `Aisha while she was six years old and consummated his marriage with her while she was nine years old and she remained with him for nine years (i.e. till his death).
Grade: Sahih

Hadith #4952 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) stayed for three days at a place between Khaibar and Medina, and there he consummated his marriage with Safiyya bint Huyay. I invited the Muslims to a banquet which included neither meat nor bread. The Prophet (ï·º) ordered for the leather dining sheets to be spread, and then dates, dried yogurt and butter were provided over it, and that was the Walima (banquet) of the Prophet. The Muslims asked whether Safiyya would be considered as his wife or as a slave girl of what his righ
Grade: Sahih

Hadith #4953 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
When the Prophet (ï·º) married me, my mother came to me and made me enter the house (of the Prophet) and nothing surprised me but the coming of Allahâs Messenger (ï·º) to me in the forenoon.
Grade: Sahih

Hadith #4954 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âDid you get Anmat?â I said, âO Allahâs Messenger (ï·º)! From where can we have Anmat?â The Prophet (ï·º) said, âSoon you will have them (Anmat).
Grade: Sahih

Hadith #4955 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
that she prepared a lady for a man from the Ansar as his bride and the Prophet said, âO âAisha! Havenât you got any amusement (during the marriage ceremony) as the Ansar like amusement?â
Grade: Sahih

Hadith #4956 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
âWhenever the Prophet (ï·º) passed by (my mother Um-Sulaim) he used to enter her and greet her. Anas further said: Once the Prophet (ï·º) way a bridegroom during his marriage with Zainab, Um Sulaim said to me, âLet us give a gift to Allahâs Messenger (ï·º) .â I said to her, âDo it.â So she prepared Haisa (a sweet dish) made from dates, butter and dried yoghurt and she sent it with me to him. I took it to him and he said, âPut it down,â and ordered me to call some men whom he name
Grade: Sahih

Hadith #4957 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
That she borrowed a necklace from Asmaâ and then it got lost. So Allahâs Messenger (ï·º) sent some people from his companions in search of it. In the meantime the stated time for the prayer became due and they offered their prayer without ablution. When they came to the Prophet, they complained about it to him, so the Verse regarding Tayammum was revealed . Usaid bin Hudair said, â(O `Aisha!) may Allah bless you with a good reward, for by Allah, never did a difficulty happen in connection
Grade: Sahih

Hadith #4958 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ï·º) said, âIf anyone of you, when having sexual intercourse with his wife, says: Bismillah, Allahumma jannibni-Sh-Shaitan wa jannib-ish-Shaitan ma razaqtana, and if it is destined that they should have a child, then Satan will never be able to harm him.â
Grade: Sahih

Hadith #4959 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
I was ten years old when Allahâs Messenger (ï·º) arrived at Medina. My mother and aunts used to urge me to serve the Prophet (ï·º) regularly, and I served him for ten years. When the Prophet (ï·º) died I was twenty years old, and I knew about the order of Al-Hijab (veiling of ladies) more than any other person when it was revealed. It was revealed for the first time when Allahâs Messenger (ï·º) had consummated his marriage with Zainab bint Jahsh. When the day dawned, the Prophet (ï·º) was a
Grade: Sahih

Hadith #4960 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
When `Abdur-Rahman bin `Auf married an Ansari woman, the Prophet (ï·º) asked him, âHow much Mahr did you give her?â `Abdur-Rahman said, âGold equal to the weight of a date stone.â Anas added: When they (i.e. the Prophet (ï·º) and his companions) arrived at Medina, the emigrants stayed at the Ansarâs houses. `Abdur-Rahman bin `Auf stayed at Sa`d bin Ar-Rabiâs house. Sa`d said to `Abdur- Rahman, âI will divide and share my property with you and will give one of my two wives to you.â
Grade: Sahih

Hadith #4961 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) did not give a better wedding banquet on the occasion of marrying any of his wives than the one he gave on marrying Zainab, and that banquet was with (consisted of) one sheep.
Grade: Sahih

Hadith #4962 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allahâs Messenger (ï·º) manumitted Safiyya and then married her, and her Mahr was her manumission, and he gave a wedding banquet with Hais (a sort of sweet dish made from butter, cheese and dates).
Grade: Sahih

Hadith #4963 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) consummated his marriage with a woman (Zainab), so he sent me to invite men to the meals.
Grade: Sahih

Hadith #4964 - Sahih al-Bukhari - Thabit Al-Bunani (Sahih al-Bukhari)
The marriage of Zainab bint Jahash was mentioned in the presence of Anas and he said, âI did not see the Prophet (ï·º) giving a better banquet on marrying any of his wives than the one he gave on marrying Zainab. He then gave a banquet with one sheep.â
Grade: Sahih

Hadith #4965 - Sahih al-Bukhari - Safiyya bint Abi 'Ubaid al-Thaqafi ØµÙÙØ© Ø¨ÙØª Ø£Ø¨Ù Ø¹Ø¨ÙØ¯ Ø¨Ù ÙØ³Ø¹ÙØ¯ Ø§ÙØ«ÙÙÙØ© (Sahih al-Bukhari)
The Prophet (ï·º) gave a banquet with two Mudds of barley on marrying some of his wives. (1 Mudd= 1 3/4 of a kilogram) .
Grade: Sahih

Hadith #4966 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âIf anyone of you is invited to a wedding banquet, he must go for it (accept the invitation).â
Grade: Sahih

Hadith #4967 - Sahih al-Bukhari - Abu Musa al-Asha'ari (Sahih al-Bukhari)
The Prophet (ï·º) said, âSet the captives free, accept the invitation (to a wedding banquet), and visit the patients.â
Grade: Sahih

Hadith #4968 - Sahih al-Bukhari - al-Bara' bin Azib bin al-Harith (Sahih al-Bukhari)
The Prophet (ï·º) ordered us to do seven (things) and forbade us from seven. He ordered us to visit the patients, to follow the funeral procession, to reply to the sneezer (i.e., say to him, âYarhamuka-l-lah (May Allah bestow His Mercy upon you), if he says âAl-hamduli l-lahâ (Praise be to Allah), to help others to fulfill their oaths, to help the oppressed, to greet (whomever one should meet), and to accept the invitation (to a wedding banquet). He forbade us to wear golden rings, to use
Grade: Sahih

Hadith #4969 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
Abu Usaid As-Saâdi invited Allahâs Messenger (ï·º) to his wedding party and his wife who was the bride, served them on that day. Do you know what drink she gave Allahâs Messenger (ï·º)? She had soaked some dates for him (in water) overnight, and when he had finished his meal she gave him that drink (of soaked dates).
Grade: Sahih

Hadith #4970 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The worst food is that of a wedding banquet to which only the rich are invited while the poor are not invited. And he who refuses an invitation (to a banquet) disobeys Allah and His Apostle .
Grade: Sahih

Hadith #4971 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âIf I am invited to a meal of trotters I will accept it; and if I am given a trotter as a present I will accept it.â
Grade: Sahih

Hadith #4972 - Sahih al-Bukhari - Nafi' b. 'Ujayr b. 'Abd Yazid b. Hashim (Sahih al-Bukhari)
`Abdullah bin `Umar said, âAllahâs Messenger (ï·º) said, âAccept the marriage invitation if you are invited to it.â â Ibn `Umar used to accept the invitation whether to a wedding banquet or to any other party, even when he was fasting.
Grade: Sahih

Hadith #4973 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Once the Prophet (ï·º) saw some women and children coming from a wedding party. He got up energetically and happily and said, âBy Allah! You (i.e., the Ansar) are the most beloved of all people to me.â
Grade: Sahih

Hadith #4974 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
(the wife of the Prophet) I bought a cushion having on it pictures (of animals). When Allahâs Messenger (ï·º) saw it, he stood at the door and did not enter. I noticed the sign of disapproval on his face and said, âO Allahâs Messenger (ï·º)! I repent to Allah and His Apostle. What sin have I committed?â Allahâs Messenger (ï·º) said. âWhat is this cushion?â I said, âI have bought it for you so that you may sit on it and recline on it.â Allahâs Messenger (ï·º) said, âThe make
Grade: Sahih

Hadith #4975 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
When Abu Usaid As-Sa`idi got married, he invited the Prophet (ï·º) and his companions. None prepared the food for them and brought it to them but his wife. She soaked some dates in water in a stone pot overnight, and when the Prophet (ï·º) had finished his food, she provided him with that drink (of soaked dates).
Grade: Sahih

Hadith #4976 - Sahih al-Bukhari - Sahl bin Sa'd bin Malik (Sahih al-Bukhari)
Abu Usaid As-Sa`idi invited the Prophet (ï·º) to his wedding party and his wife served him on that day, and she was the bride. She said (or Sahl said), âDo you know what she soaked for Allahâs Messenger (ï·º)? She soaked some dates for him (in water) in a drinking bowl overnight.â
Grade: Sahih

Hadith #4977 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThe woman is like a rib; if you try to straighten her, she will break. So if you want to get benefit from her, do so while she still has some crookedness.â
Grade: Sahih

Hadith #4978 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhoever believes in Allah and the Last Day should not hurt (trouble) his neighbor. And I advise you to take care of the women, for they are created from a rib and the most crooked portion of the rib is its upper part; if you try to straighten it, it will break, and if you leave it, it will remain crooked, so I urge you to take care of the women.â
Grade: Sahih

Hadith #4979 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
During the lifetime of the Prophet (ï·º) we used to avoid chatting leisurely and freely with our wives lest some Divine inspiration might be revealed concerning us. But when the Prophet (ï·º) had died, we started chatting leisurely and freely (with them).
Grade: Sahih

Hadith #4980 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
The Prophet (ï·º) said, âEveryone of you is a guardian and everyone of you is responsible (for his wards). A ruler is a guardian and is responsible(for his subjects); a man is a guardian of his family and responsible (for them); a wife is a guardian of her husbandâs house and she is responsible (for it), a slave is a guardian of his masterâs property and is responsible (for that). Beware! All of you are guardians and are responsible (for your wards).
Grade: Sahih

Hadith #4981 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Eleven women sat (at a place) and promised and contracted that they would not conceal anything of the news of their husbands. The first one said, âMy husband is like the meat of a slim weak camel which is kept on the top of a mountain which is neither easy to climb, nor is the meat fat, so that one might put up with the trouble of fetching it.â The second one said, âI shall not relate my husbandâs news, for I fear that I may not be able to finish his story, for if I describe him, I will
Grade: Sahih

Hadith #4982 - Sahih al-Bukhari - 'Urwa Al-Bariqi (Sahih al-Bukhari)
Aisha said, âWhile the Ethiopians were playing with their small spears, Allahâs Messenger (ï·º) screened me behind him and I watched (that display) and kept on watching till I left on my own.â So you may estimate of what age a little girl may listen to amusement.
Grade: Sahih

Hadith #4983 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
I had been eager to ask `Umar bin Al-Khattab about the two ladies from among the wives of the Prophet regarding whom Allah said âIf you two (wives of the Prophet (ï·º) namely Aisha and Hafsa) turn in repentance to Allah, your hearts are indeed so inclined (to oppose what the Prophet (ï·º) likes). (66.4) till `Umar performed the Hajj and I too, performed the Hajj along with him. (On the way) `Umar went aside to answer the call of nature, and I also went aside along with him carrying a tumbler f
Grade: Sahih

Hadith #4984 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âA woman should not fast (optional fasts) except with her husbandâs permission if he is at home (staying with her).
Grade: Sahih

Hadith #4985 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âIf a man Invites his wife to sleep with him and she refuses to come to him, then the angels send their curses on her till morning.â
Grade: Sahih

Hadith #4986 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ï·º) said, âIf a woman spends the night deserting her husbandâs bed (does not sleep with him), then the angels send their curses on her till she comes back (to her husband).
Grade: Sahih

Hadith #4987 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âIt is not lawful for a lady to fast (Nawafil) without the permission of her husband when he is at home; and she should not allow anyone to enter his house except with his permission; and if she spends of his wealth (on charitable purposes) without being ordered by him, he will get half of the reward.â
Grade: Sahih

Hadith #4988 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
The Prophet (ï·º) said, âI stood at the gate of Paradise and saw that the majority of the people who entered it were the poor, while the wealthy were stopped at the gate (for the accounts). But the companions of the Fire were ordered to be taken to the Fire. Then I stood at the gate of the Fire and saw that the majority of those who entered it were women.â
Grade: Sahih

Hadith #4989 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
During the lifetime of Allahâs Messenger (ï·º), the sun eclipsed. Allahâs Messenger (ï·º) offered the prayer of (the) eclipse) and so did the people along with him. He performed a long Qiyam (standing posture) during which Surat-al-Baqara could have been recited; then he performed a pro-longed bowing, then raised his head and stood for a long time which was slightly less than that of the first Qiyam (and recited Qurâan). Then he performed a prolonged bowing again but the period was shorter
Grade: Sahih

Hadith #4990 - Sahih al-Bukhari - Imran al-Barqy Ø¹ÙØ±Ø§Ù Ø§ÙØ¨Ø§Ø±ÙÙ (Sahih al-Bukhari)
The Prophet (ï·º) said, âI looked at Paradise and saw that the majority of its residents were the poor; and I looked at the (Hell) Fire and saw that the majority of its residents were women.â
Grade: Sahih

Hadith #4991 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âO `Abdullah! Have I not been formed that you fast all the day and stand in prayer all night?â I said, âYes, O Allahâs Messenger (ï·º)!â He said, âDo not do that! Observe the fast sometimes and also leave them (the fast) at other times; stand up for the prayer at night and also sleep at night. Your body has a right over you, your eyes have a right over you and your wife has a right over you.â
Grade: Sahih

Hadith #4992 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
The Prophet (ï·º) said, âAll of you are guardians and are responsible for your wards. The ruler is a guardian and the man is a guardian of his family; the lady is a guardian and is responsible for her husbandâs house and his offspring; and so all of you are guardians and are responsible for your wards.â
Grade: Sahih

Hadith #4993 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allahâs Messenger (ï·º) took an oath that he would not visit his wives for one month, and he sat in an upper room belonging to him. Then, on the twenty ninth day he came down. It was said, âO Allahâs Messenger (ï·º)! You had taken an oath not to visit your wives for one month.â He said, âThe (present) month is of twenty-nine days.â
Grade: Sahih

Hadith #4994 - Sahih al-Bukhari - Umm Salamah (Sahih al-Bukhari)
The Prophet (ï·º) took an oath that he would not enter upon some of his wives for one month. But when twenty nine days had elapsed, he went to them in the morning or evening. It was said to him, âO Allahâs Prophet! You had taken an oath that you would not enter upon them for one month.â He replied, âThe month can be of twenty nine days.â
Grade: Sahih

Hadith #4995 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
One morning we saw the wives of the Prophet (ï·º) weeping, and everyone of them had her family with her, I went to the mosque and found that it was crowded with people. Then `Umar bin Al-Khattab came and went up to the Prophet (ï·º) who was in his upper room. He greeted him but nobody answered. He greeted again, but nobody answered. Then the gatekeeper called him and he entered upon the Prophet, and asked, âHave you divorced your wives?â The Prophet, said, âNo, but I have taken an oath not
Grade: Sahih

Hadith #4996 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
The Prophet (ï·º) said, âNone of you should flog his wife as he flogs a slave and then have sexual intercourse with her in the last part of the day.â
Grade: Sahih

Hadith #4997 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
An Ansari woman gave her daughter in marriage and the hair of the latter started falling out. The Ansari women came to the Prophet (ï·º) and mentioned that to him and said, âHer (my daughterâs) husband suggested that I should let her wear false hair.â The Prophet (ï·º) said, âNo, (donât do that) for Allah sends His curses upon such ladies who lengthen their hair artificially.â
Grade: Sahih

Hadith #4998 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
regarding the Verse: âIf a wife fears cruelty or desertion on her husbandâs part â¦â) (4.128) It concerns the woman whose husband does not want to keep her with him any longer, but wants to divorce her and marry some other lady, so she says to him: âKeep me and do not divorce me, and then marry another woman, and you may neither spend on me, nor sleep with me.â This is indicated by the Statement of Allah: âThere is no blame on them if they arrange an amicable settlement between them
Grade: Sahih

Hadith #4999 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
We used to practice coitus interrupt us during the lifetime of Allahâs Messenger (ï·º) .
Grade: Sahih

Hadith #5000 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
We used to practice coitus interrupt us while the Qurâan was being revealed. Jabir added: We used to practice coitus interrupt us during the lifetime of Allahâs Messenger (ï·º) while the Qurâan was being Revealed.
Grade: Sahih

Hadith #5001 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
We got female captives in the war booty and we used to do coitus interruptus with them. So we asked Allahâs Messenger (ï·º) about it and he said, âDo you really do that?â repeating the question thrice, âThere is no soul that is destined to exist but will come into existence, till the Day of Resurrection.â
Grade: Sahih

Hadith #5002 - Sahih al-Bukhari (Sahih al-Bukhari)
Aisha said that whenever the Prophet (ï·º) intended to go on a journey, he drew lots among his wives (so as to take one of them along with him). During one of his journeys the lot fell on `Aisha and Hafsa. When night fell the Prophet (ï·º) would ride beside `Aisha and talk with her. One night Hafsa said to `Aisha, âWonât you ride my camel tonight and I ride yours, so that you may see (me) and I see (you) (in new situation)?â `Aisha said, âYes, (I agree.)â So `Aisha rode, and then the P
Grade: Sahih

Hadith #5003 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Sauda bint Zam`a gave up her turn to me (`Aisha), and so the Prophet (ï·º) used to give me (`Aisha) both my day and the day of Sauda.
Grade: Sahih

Hadith #5004 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The tradition, (of the Prophet) is that if someone marries a virgin and he has already a matron wife (with him), then he should stay with the virgin for seven days; and if someone marries a matron (and he has already a virgin wife with him) then he should stay with her for three days.
Grade: Sahih

Hadith #5005 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
It is the Prophetâs tradition that if someone marries a virgin and he has already a matron wife then he should stay for seven days with her (the virgin) and then by turns; and if someone marries a matron and he has already a virgin wife then he should stay with her (the matron) for three days, and then by turns.
Grade: Sahih

Hadith #5006 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ï·º) used to pass by (have sexual relation with) all his wives in one night, and at that time he had nine wives.
Grade: Sahih

Hadith #5007 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Whenever Allahâs Messenger (ï·º) finished his `Asr prayer, he would enter upon his wives and stay with one of them. One day he went to Hafsa and stayed with her longer than usual.
Grade: Sahih

Hadith #5008 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
that during his fatal ailment, Allahâs Messenger (ï·º), used to ask his wives, âWhere shall I stay tomorrow? Where shall I stay tomorrow?â He was looking forward to Aishaâs turn. So all his wives allowed him to stay where he wished, and he stayed at `Aishaâs house till he died there. `Aisha added: He died on the day of my usual turn at my house. Allah took him unto Him while his head was between my chest and my neck and his saliva was mixed with my saliva.
Grade: Sahih

Hadith #5009 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
that `Umar entered upon Hafsa and said, âO my daughter! Do not be misled by the manners of her who is proud of her beauty because of the love of Allahâs Messenger (ï·º) for her.â By âherâ he meant `Aisha. `Umar added, âThen I told that to Allahâs Messenger (ï·º) and he smiled (on hearing that).
Grade: Sahih

Hadith #5010 - Sahih al-Bukhari - Asma bint 'Umays (Sahih al-Bukhari)
Some lady said, âO Allahâs Messenger (ï·º)! My husband has another wife, so it is sinful of me to claim that he has given me what he has not given me (in order to tease her)?â Allahâs Messenger (ï·º) said, The one who pretends that he has been given what he has not been given, is just like the (false) one who wears two garments of falsehood.â
Grade: Sahih

Hadith #5011 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
The Prophet, said, âThere is none having a greater sense of Ghira than Allah. And for that He has forbidden the doing of evil actions (illegal sexual intercourse etc.) There is none who likes to be praised more than Allah does.â
Grade: Sahih

Hadith #5012 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âO followers of Muhammad! There is none, who has a greater sense of Ghira (self-respect) than Allah, so He has forbidden that His slave commits illegal sexual intercourse or His slave girl commits illegal sexual intercourse. O followers of Muhammad! If you but knew what I know, you would laugh less and weep more!â
Grade: Sahih

Hadith #5013 - Sahih al-Bukhari - Asma bint 'Umays (Sahih al-Bukhari)
I heard Allahâs Messenger (ï·º) saying, âThere is nothing (none) having a greater sense of Ghira (self-respect) than Allah.â And narrated Abu Huraira that he heard the Prophet (saying the same).
Grade: Sahih

Hadith #5014 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet; said, âAllah has a sense of Ghira, and Allahâs sense of Ghira is provoked when a believer does something which Allah has prohibited.â
Grade: Sahih

Hadith #5015 - Sahih al-Bukhari - Asma bint 'Umays (Sahih al-Bukhari)
When Az-Zubair married me, he had no real property or any slave or anything else except a camel which drew water from the well, and his horse. I used to feed his horse with fodder and drew water and sew the bucket for drawing it, and prepare the dough, but I did not know how to bake bread. So our Ansari neighbors used to bake bread for me, and they were honorable ladies. I used to carry the date stones on my head from Zubairâs land given to him by Allahâs Messenger (ï·º) and this land was tw
Grade: Sahih

Hadith #5016 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
While the Prophet (ï·º) was in the house of one of his wives, one of the mothers of the believers sent a meal in a dish. The wife at whose house the Prophet (ï·º) was, struck the hand of the servant, causing the dish to fall and break. The Prophet (ï·º) gathered the broken pieces of the dish and then started collecting on them the food which had been in the dish and said, âYour mother (my wife) felt jealous.â Then he detained the servant till a (sound) dish was brought from the wife at whose
Grade: Sahih

Hadith #5017 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
The Prophet, said, âI entered Paradise and saw a palace and asked whose palace is this? They (the Angels) said, âThis palace belongs to `Umar bin Al-Khattab.â I intended to enter it, and nothing stopped me except my knowledge about your sense of Ghira (self-respect (O `Umar).â `Umar said, âO Allahâs Messenger (ï·º)! Let my father and mother be sacrificed for you! O Allahâs Prophet! How dare I think of my Ghira (self-respect) being offended by you?â
Grade: Sahih

Hadith #5018 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
While we were sitting with Allahâs Messenger (ï·º), (he) Allahâs Messenger (ï·º) said, âWhile I was sleeping, I saw a woman performing ablution beside a palace. I asked, âWhose palace is this?â It was said, âThis palace belongs to `Umar.â Then I remembered his sense of Ghira and returned.â On that `Umar started weeping in that gathering and said, âO Allahâs Messenger (ï·º)! How dare I think of my self-respect being offended by you?â
Grade: Sahih

Hadith #5019 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
That Allahâs Messenger (ï·º) said to her, âI know when you are pleased with me or angry with me.â I said, âWhence do you know that?â He said, âWhen you are pleased with me, you say, âNo, by the Lord of Muhammad,â but when you are angry with me, then you say, âNo, by the Lord of Abraham.â â Thereupon I said, âYes (you are right), but by Allah, O Allahâs Messenger (ï·º), I leave nothing but your name.â
Grade: Sahih

Hadith #5020 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
I never felt so jealous of any wife of Allahâs Messenger (ï·º) as I did of Khadija because Allahâs Messenger (ï·º) used to remember and praise her too often and because it was revealed to Allahâs Messenger (ï·º) that he should give her (Khadija) the glad tidings of her having a palace of Qasab in Paradise .
Grade: Sahih

Hadith #5021 - Sahih al-Bukhari - al-Miswar bin Makhrama bin Nawfal (Sahih al-Bukhari)
I heard Allahâs Messenger (ï·º) who was on the pulpit, saying, âBanu Hisham bin Al-Mughira have requested me to allow them to marry their daughter to `Ali bin Abu Talib, but I donât give permission, and will not give permission unless `Ali bin Abi Talib divorces my daughter in order to marry their daughter, because Fatima is a part of my body, and I hate what she hates to see, and what hurts her, hurts me.â
Grade: Sahih

Hadith #5022 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
I will narrate to you a Habith I heard from Allahâs Messenger (ï·º) and none other than I will tell you of it. I heard Allahâs Messenger (ï·º) saying, âFrom among the portents of the Hour are the following: Religious knowledge will be taken away; General ignorance (in religious matters) will increase; illegal Sexual intercourse will prevail: Drinking of alcoholic drinks will prevail. Men will decrease in number, and women will increase in number, so much so that fifty women will be looked
Grade: Sahih

Hadith #5023 - Sahih al-Bukhari - Uqba bin 'Amir al-Juhayni (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âBeware of entering upon the ladies.â A man from the Ansar said, âAllahâs Apostle! What about Al-Hamu the in-laws of the wife (the brothers of her husband or his nephews etc.)?â The Prophet (ï·º) replied: The in-laws of the wife are death itself.
Grade: Sahih

Hadith #5024 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ï·º) said, âNo man should stay with a lady in seclusion except in the presence of a Dhu- Muhram.â A man stood up and said, âO Allahâs Messenger (ï·º)! My wife has gone out intending to perform the Hajj and I have been enrolled (in the army) for such-and-such campaign.â The Prophet (ï·º) said, âReturn and perform the Hajj with your wife.â
Grade: Sahih

Hadith #5025 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
An Ansari woman came to the Prophet (ï·º) and he took her aside and said (to her). âBy Allah, you (Ansar) are the most beloved people to me.â
Grade: Sahih

Hadith #5026 - Sahih al-Bukhari - Umm Salamah (Sahih al-Bukhari)
that while the Prophet (ï·º) was with her, there was an effeminate man in the house. The effeminate man said to Um Salamaâs brother, `Abdullah bin Abi Umaiyya, âIf Allah should make you conquer Taâif tomorrow, I recommend that you take the daughter of Ghailan (in marriage) for (she is so fat) that she shows four folds of flesh when facing you and eight when she turns her back.â Thereupon the Prophet (ï·º) said (to us), âThis (effeminate man) should not enter upon you (anymore).
Grade: Sahih

Hadith #5027 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
The Prophet (ï·º) was screening me with his Ridaâ (garment covering the upper part of the body) while I was looking at the Ethiopians who were playing in the courtyard of the mosque. (I continued watching) till I was satisfied. So you may deduce from this event how a little girl (who has not reached the age of puberty) who is eager to enjoy amusement should be treated in this respect.
Grade: Sahih

Hadith #5028 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Once Sa`da bint Zam`a went out at night for some need, and `Umar saw her, and recognizing her, he said (to her), âBy Allah, O Sa`da! You cannot hide yourself from us.â So she returned to the Prophet (ï·º) and mentioned that to him while he was sitting in my dwelling taking his supper and holding a bone covered with meat in his hand. Then the Divine Inspiration was revealed to him and when that state was over, he (the Prophet (ï·º) was saying: âO women! You have been allowed by Allah to go
Grade: Sahih

Hadith #5029 - Sahih al-Bukhari - Salim's father (Sahih al-Bukhari)
The Prophet (ï·º) said, âIf the wife of anyone of you asks permission to go to the mosque, he should not forbid her.â
Grade: Sahih

Hadith #5030 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
My foster uncle came and asked permission (to enter) but I refused to admit him till I asked Allahâs Apostle about that. He said, âHe is your uncle, so allow him to come in.â I said, âO Allahâs Messenger (ï·º)! I have been suckled by a woman and not by a man.â Allahâs Messenger (ï·º) said, âHe is your uncle, so let him enter upon you.â And that happened after the order of Al-Hijab (compulsory veiling) was revealed. All things which become unlawful because of blood relations are
Grade: Sahih

Hadith #5031 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
The Prophet (ï·º) said, âA woman should not look at or touch another woman to describe her to her husband in such a way as if he was actually looking at her.â
Grade: Sahih

Hadith #5032 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
The Prophet (ï·º) said, âA woman should not look at or touch another woman to describe her to her husband in such a way as if he was actually looking at her.â
Grade: Sahih

Hadith #5033 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
(The Prophet) Solomon son of (the Prophet) David said, âTonight I will go round (i.e. have sexual relations with) one hundred women (my wives) everyone of whom will deliver a male child who will fight in Allahâs Cause.â On that an Angel said to him, âSay: âIf Allah will.â â But Solomon did not say it and forgot to say it. Then he had sexual relations with them but none of them delivered any child except one who delivered a half person. The Prophet (ï·º) said, âIf Solomon had said
Grade: Sahih

Hadith #5034 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
The Prophet (ï·º) disliked that one should go to oneâs family at night (on returning from a journey).
Grade: Sahih

Hadith #5035 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âWhen anyone of you is away from his house for a long time, he should not return to his family at night.â
Grade: Sahih

Hadith #5036 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
I was with Allahâs Messenger (ï·º) in a Ghazwa, and when we returned, I wanted to hurry, while riding a slow camel. A rider came behind me. I looked back and saw that the rider was Allahâs Messenger (ï·º) . He said (to me), âWhat makes you in such a hurry?â I replied, âI am newly married.â He said, âDid you marry a virgin or a matron?â I replied, â(Not a virgin but) a matron.â He said, âWhy didnât you marry a young girl with whom you could play and who could play with you
Grade: Sahih

Hadith #5037 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
The Prophet (ï·º) said, âIf you enter (your town) at night (after coming from a journey), do not enter upon your family till the woman whose husband was absent (from the house) shaves her pubic hair and the woman with unkempt hair, combs her hairâ Allahâs Messenger (ï·º) further said, â(O Jabir!) Seek to have offspring, seek to have offspring!â
Grade: Sahih

Hadith #5038 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
We were with the Prophet (ï·º) in Ghazwa, and when we returned and approached Medina, I wanted to hurry while riding a slow camel. A rider overtook me and pricked my camel with a spear which he had, whereupon my camel started running as fast as any other fast camel you may see. I looked back, and behold, the rider was Allahâs Messenger (ï·º) . I said, âO Allahâs Messenger (ï·º)! I am newly married â He asked, âHave you got married?â I replied, âYes.â He said, âA virgin or a mat
Grade: Sahih

Hadith #5039 - Sahih al-Bukhari - Abu Hazim al-Bajli (Sahih al-Bukhari)
The people differed about the type of treatment which had been given to Allahâs Messenger (ï·º) on the day (of the battle) of Uhud. So they asked Sahl bin Sa`d As-Sa`id who was the only surviving Companion (of the Prophet) at Medina. He replied, âNobody Is left at Medina who knows it better than I. Fatima was washing the blood off his face and `Ali was bringing water in his shield, and then a mat of datepalm leaves was burnt and (the ash) was inserted into the wound.â
Grade: Sahih

Hadith #5040 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
I heard Ibn `Abbas answering a man who asked him, âDid you attend the prayer of `Id al Adha or `Idal- Fitr with Allahâs Messenger (ï·º)?â Ibn `Abbas replied, âYes, and had it not been for my close relationship with him, I could not have offered it.â (That was because of his young age). Ibn `Abbas further said, Allahâs Messenger (ï·º) went out and offered the Id prayer and then delivered the sermon.â Ibn `Abbas did not mention anything about the Adhan (the call for prayer) or the Iq
Grade: Sahih

Hadith #5041 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Abu Bakr admonished me and poked me with his hands in the flank, and nothing stopped me from moving at that time except the position of Allahâs Messenger (ï·º) whose head was on my thigh.
Grade: Sahih